Silviculture Research in India - Rawat, G. S.; Dhiman, R. C. (Indian Forester, 2002)
Silviculture research has rendered yeoman service to the development of forestry and forestry practices in India. Important research achievements in silviculture have been the study of woody plants , classification of forest types , development of silvicultural systems and afforestation techniques , introduction of exotics and management of bamboos. SilvicuIturists are likely to face complex challenges of sustainable forest .management , biodiversity conservation and joint forest management. Silvicultural options are therefore required to be developed to address these complex and other technological issues.